Ocean Cooling Pattern at the Last Glacial Maximum - Kelin Zhuang; John R. Giardino (Advances in Meteorology, 2012)
Ocean temperature and ocean heat content change are analyzed based on four PMIP3 model results at the Last Glacial Maximum relative to the prehistorical run. Ocean cooling mostly occurs in the upper 1000 m depth and varies spatially in the tropical and temperate zones. The Atlantic Ocean experiences greater cooling than the rest of the ocean basins. Ocean cooling is closely related to the weakening of meridional overturning circulation and enhanced intrusion of Antarctic Bottom Water into the North Atlantic.